Configuração da gestão da educação a distância: entendendo os resultados do ENADE para o curso piloto da universidade aberta do Brasil - Serra, Antonio Roberto Coelho (2012)
Distance education has been having an expressive growth in Brazil in the last years and together with this expansion it also increases the challenges related to its management. This work focuses on the many conceptions and theoretical elements about the approaches on organizational structures and systems of distance education for the conception of what has been nominated as management of DE. As a research design, it was analyzed the relationship between the configuration of management of distance course in Business Management – a pilot project of Universidade Aberta do Brasil (Open University of Brazil) and its concepts defined by the Exame Nacional de Desempenho de Estudantes (Students Development National Exam) – identifying the theories and patterns manifested in its context. The work comes from a description of the organizational structure of the area that is responsible for the Distance Education at the Universidade Estadual do Maranhão, at the Universidade Estadual da Paraíba and at the Universidade Federal do Ceará. It makes a comparative analysis of complexity, centralization and coordination in these three institutions. It was also analyzed and compared the DE systems of the pilot course at UAB (OUB) from the quality referential for higher distance education from MEC, specifically concentrated on interdisciplinary, learning materials, evaluation, multidisciplinary team, communication and structure of centers. Based on these analysis it is discussed the different concepts given by Enade to the referred courses and it is explained the relation of the organizational structures and the described DE system, in relation to these results. It is a qualitative, descriptive, explicative and multicase research, which the data collection was made through interviews, focal groups, online questionnaires and documents. The primary data were treated by category content analysis, and the secondary was made by documental analysis. The observation elaborated inside a descriptive, interpretative perception andof a sectional cut allows inductions around the configuration of management in each university. It is evidenced the strong and direct relationship between the configuration of pilot course management sand the respective Enade results. It is found that the industrialization theory of Otto Peters and the distance education model based on the distribution of centers can explain the translated structuralization of o modus operandi of Universidade Aberta do Brasil. Therefore it is concluded that the differences on the Enade results of Uema, UEPB and UFC students have direct relation to the way of structuring the departments in charge of intermediating the DE in these universities. It is found that the pilot course of UAB at UEPB has not demonstrated to have the necessary adherence to quality references of MEC, while Uema and UFC have demonstrated a great adequacy to the established criteria, what confirms the relation between such quality references and the Enade result. It is also concluded that the evaluation components and multidisciplinary team were the one that most suggested relationship with the development of students at Enade. The results were discussed to the light of the theory reviewed referential and were presented recommendations that come from the findings of this research.